If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1d + 15 = 11 Reorder the terms: 15 + -1d = 11 Solving 15 + -1d = 11 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -1d = 11 + -15 Combine like terms: 15 + -15 = 0 0 + -1d = 11 + -15 -1d = 11 + -15 Combine like terms: 11 + -15 = -4 -1d = -4 Divide each side by '-1'. d = 4 Simplifying d = 4
| 9(a+8)=135 | | 16x^2-16x-35=0 | | 1=2c-9 | | 8e-2=22 | | 16x^2-8x-8x+4=39 | | 3.4=-13.6+(-3.4c)+1.7 | | 0.20y-0.4=0.10y+2-0.5y | | 60x^2+34x-70=0 | | x(5x+2)=2x^2-2x+4 | | 16x^2+28x+6=0 | | 6n-9=-16+n | | (-10u^4+5)-(-2u^4-8)=0 | | -12b^2+26b+56=0 | | 832-n=325 | | x-0.7=8.24 | | 56w^2-17w-3=0 | | 17s=136 | | x^2-84x+83=0 | | 2x^2-6x+9=20 | | 12+1.5x=6x | | 32xy^2-80xy+50x= | | x^2+kx+24= | | (1.5)(x+8)=6x | | 4(-2)z+8(-2)+4(-2)+6= | | 1*p=5 | | 4s-20=-28+2s | | 6z-4=28+3z | | 6(3+2x)-2=52 | | 8h^2-2h-3=63 | | 6a^3+13a^2+5a=0 | | ab-ac-3b+3c=0 | | -0.7x+1.5=-1.1-1.1x |